Determination of LC50 and histopathological changes due to endosulfan in beluga (Huso huso) - Sharifpour, I.; Soltani, M.; Javadi, M. (2004)
This study was conducted in order to determine the LC50 of organochlorine insecticide, Endosulfan, lethal limit, Maximum Allowable Toxicant Concentration (MATC), clinical signs and histopathological changes in vital organs due to the toxic effects of the toxin on beluga (Huso huso). The experimental investigation was done at 20°C water temperature using 35% emulsion of ndusolfan and Organisation Economic Cooperation and Development (OECD) method. For this purpose 150 specimens of this species with 3-5g body weight were used in static water quality condition during 4 days. A LC50 of 0.0063, 0.0016, 0.0006 and 0.0003 ppm and also a MATC of 0.00063, 0.00016, 0.00006 and 0.00003 ppm, were determined at 24, 48, 72 and 96 hours post exposing, respectively. The affected fish showed irregular swimming, whirlling, convulsion and bottom sitting behaviours as well as pale colour and respiratory disorders resulted in a short time death specially in high concenteration of endosulfan. Histopathologically, hyperaemia, swelling and separating basement membrane of gill lamellae were evident in fishes exposed to high concenteration (≥1ppm) of endosulfan. Also congestion, and necrosis of kidney, blood congestion, hepatocytes degeneration and to some extent, necrosis were observed in the liver of affected fishes. According to the lethal limit and LC50 results (< %0.1), this insecticide should be considered as a very high toxic (VHT) chemical substance for beluga fingerlings causing a rapid and accumulative mortality in this species.